2018
DOI: 10.20944/preprints201810.0673.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Poly-ADP Ribosyl Polymerase 1 (PARP1) Regulates Influenza A Virus Polymerase

Abstract: Influenza A viruses (IAV) are evolutionarily successful pathogens, capable of infecting a number of avian and mammalian species, and responsible for pandemic and seasonal epidemic disease in humans. To infect new species, IAV typically must overcome a number of species barriers to entry, replication, and egress, even while virus replication is counter-acted by antiviral host factors and innate immune mechanisms. A number of host factors have been found to regulate the replication of IAV by interacting with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Besides the known roles for the PARP1 and PARP2 enzymes in DNA repair (14,15), members of the PARP family have numerous additional functions (16). The 18 known human PARPs appear to differentially affect viral replication; some exhibit proviral activity and others exhibit antiviral roles (7,(17)(18)(19)(20)(21). In coronavirus, the N protein is mono (ADP) ribosylated (MARylated) during infection.…”
Section: Importancementioning
confidence: 99%
“…Besides the known roles for the PARP1 and PARP2 enzymes in DNA repair (14,15), members of the PARP family have numerous additional functions (16). The 18 known human PARPs appear to differentially affect viral replication; some exhibit proviral activity and others exhibit antiviral roles (7,(17)(18)(19)(20)(21). In coronavirus, the N protein is mono (ADP) ribosylated (MARylated) during infection.…”
Section: Importancementioning
confidence: 99%
“…It has been reported that efficient HIV-1 (Human Immunodeficiency Virus-1) integration and transcriptional activation also require PARP1 activity (Ha et al, 2001;Yu, Liu, Yang, & Zhou, 2018). Recently, PARP1 was shown as a cofactor in the activity of the influenza A virus polymerase (Westera et al, 2019). In another study, Shou et al showed that PARP1 functions as a regulator of NF-kB by promoting its nuclear translocation and by facilitating its binding to the NF-kB response sequences in macrophages upon vaccinia virus infection; therefore PARP1 can provide viral control through natural killer (NK) cell recruitment to the site of infection (Shou, Fu, Huang, Yang, 2019)…”
Section: Viral Infectionsmentioning
confidence: 99%
“…PARP1 is observed to be a facilitator of influenza A virus (IAV) infection through regulation of RNA dependent RNA polymerase (Rdrp polymerase) of influenza A virus. However, endogenous PARylation inhibited Rdrp assembly (Westera et al, 2019). Host protein PARP1 is reported to facilitate propagation of influenza A virus through degradation of interferon receptor type I (IFNAR) (Xia et al, 2020).…”
Section: Parp1 and Viral Infectionmentioning
confidence: 99%